Marketing Strategies For Increased Product Sales MSMEs Sari Boga Ayu Matrijeron Village, Matrijeron District, Yogyakarta City - Fx. Pudjo Wibowo; Eso Hernawan (LPPM Universitas Buddhi Dharma, 2025)
Marketing Strategies For Increasing Product Sales to find out the influence both individually and jointly between independent variables on dependent variables. The research was conducted in Sari Boga Ayu MSMEs, Matrijeron Village, Matrijeron District, Yogyakarta City, distributing a questionnaire of questions while the research sample was randomly sampling. R2 87.9% contribution of independent variables to the dependent variable of MSMEs Sari Boga Ayu Matrijeron Village, Matrijeron District, Yogyakarta City is 87.9% 12.1% the rest excluding other factors of independent variables., F count 172,359 sig= 0.000 and F table 3.87 F count > F table 172,359 > 3.87 probability values 0.000 < 0.05, stated that the independent variables simultaneously had a close potential relationship and had a significant effect on the dependent variable of MSMEs Sari Boga Ayu Matrijeron Village, Matrijeron District, Yogyakarta City and Product b1 = 0, .531, t count 6,369 > t table 1.65 and sig. 0000 < 0.05, price b2= 0, .548, t count 3.559 > t table 1.65 and .sig.0001 < 0.05, distribution b3= 0, 613, t count 5.904 > t table 1.65 and . sig. 0000 < 0.05 and promotion b4= 0, 329, t count 4.648 > t table 1.65 and sig. 0000 < 0.05 This independent variable has a close potential relationship and has a significant effect on the dependent variable of MSMEs Sari Boga Ayu Matrijeron Village, Matrijeron District, Yogyakarta City.